THE EFFECTS OF TRUST, STORE IMAGE AND CONSUMER JUDGMENT ON REPEAT PURCHASES MEDIATING CONSUMER SATISFACTION VARIABLES ALFAMIDI DEMAK AREA - Wibowo, Aditya Angger (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The purpose of this study was to determine how much influence trust, store image and consumer judgment have on repeat purchases through customer satisfaction, because Alfamid customers are the mediator of research. The population of the people taken in the study is the number of Alfamidi customers in the Demak area, the exact number of which is unknown, the sampling technique of course uses purposive sampling, where the sample size is 110 consumer representatives. The validity and reliability criteria applied in this study also use Amos free calculations for data analysis and calculation. The main conclusions of this study are that trust has a positive and significant impact on customer satisfaction; customer satisfaction is positively affected by store image and also positively affects customer satisfaction; consumer judgment is positively affected by customer satisfaction but does not significantly affect customer satisfaction. trust has a positive and significant impact in relation to repeat purchases.Store image has a positive, but not significant impact in relation to repeat purchases; consumer judgment has a positive, but not significant impact in relation to repeat purchases. Consumer satisfaction has a positive and significant impact on repeat purchase behavior. trust has a positive and significant impact on the purchase of goods through consumer satisfaction feedback, while store image has a positive and significant impact on the purchase of goods through consumer consumer feedback, and consumer judgment evaluation has a positive and significant impact on the repurchase of goods through consumer satisfaction feedback